Re-moulding publication criteria for the advancement of medical faculty: a wake-up call for medical fraternity - Subramanian, Subhiksha; Prabath, Indumathi; Raja, Sangeetha (International Journal of Basic & Clinical Pharmacology, 2022)
Sir, The National Medical Commission (NMC) is a dynamic organization constituted to revamp medical education all over the nation by imparting changes in the medical curriculum and criteria for teaching faculty. The core objective of recent regulations on teachers eligibility qualifications in Medical Institutions, 2022 is to promote a uniform teaching standard among medical institutions functioning under the scope of NMC.